Soil Solution Nutrient Availability, Nutritional Status and Yield of Corn Grown in a Typic Hapludox under Twelve Years of Pig Slurry Fertilizations - Grohskopf, Marco Andre [UNESP]; Cassol, Paulo Cezar; Correa, Juliano Corulli; Albuquerque, Jackson Adriano; Ernani, Paulo Roberto; Heberle Mafra, Maria Sueli; Mafra, Alvaro Luiz (Soc Brasileira De Ciencia Do Solo, 2016)
Nutrient content in soil solution may vary in response to the applied amount of pig slurry (PS). Thus, the aim of this research was to evaluate the nutrient content in soil solution and its relationship to nutritional status and yield of corn under 12 years of annual fertilization with increasing doses of PS, soluble mineral fertilizer (MF) and PS combined with MF. The experiment was conducted under field conditions in a Latossolo Vermelho Distroferrico (Typic Hapludox). The treatments consisted of pig slurry at annual rates of 50 and 100 m3 ha(-1) (PS50 and PS100), soluble mineral fertilizer (MF), and pig slurry at a rate of 25 m3 ha(-1) complemented with mineral fertilizer (PS25 + MF), distributed in a randomized block design. Soil solution was sampled at two depths, 0.40 and 0.80 m, on six dates after the fertilizer applications. The nitrate (NO3--N) and K levels in the soil solution were measured 40, 108 and 135 days after the last application of fertilizer (DAAF), being subsequently correlated with corn yield. PS50 provide contents of NO3--N, P and K to the soil solution similar to those supplied by MF or PS25+MF. The critical limit of 10 mg L-1 NO3--N in the soil solution was exceeded on 108, 135 and 230 DAAF, at rates of 100 and 50 m(3) ha(1) of PS and on 230 DAAF when using MF.
Keywords: organic fertilizer; manure; leaching